Evaluation of Modeling Approaches for MILD Combustion Systems With Internal Recirculation - Amaduzzi, Ruggero; Ceriello, Giuseppe; Ferrarotti, Marco; Sorrentino, Giancarlo; Parente, Alessandro (Frontiers in Mechanical Engineering, 2020)
Numerical simulations employing two different modeling approaches are performed and validated against experimental results from a moderate or intense low-oxygen dilution (MILD) system with internal recirculation. The flamelet-generated manifold (FGM) and partially stirred reactor (PaSR) closures are employed in a Reynolds-averaged Navier–Stokes (RANS) framework to carry out the numerical simulations. The results show that the FGM model strongly overpredicts temperature profiles in the reactive region, while yielding better results along the central thermocouple. The PaSR closures based on a prescribed mixing time constant, Cmix, of 0.01, 0.1, and 0.5 are compared, showing that a Cmix value of 0.5 is the most appropriate choice for the cases under investigation. A PaSR formulation allowing local estimation of the Cmix value is found to provide improved results for both the lateral and central thermocouples. A flame index analysis, used to assess the ability of FGM and PaSR to capture intense mixing of the cyclonic burner, indicates how the FGM model predicts a typical non-premixed region after the injection zone, contrary to the experimental observation.